Implementing rural development projects : lessons from AID and World Bank experiences - Morss, Elliott R.; Gow, David D. (Boulder, Colo. : Westview Press, 1985)
This book analyzes critical problems encountered at the level of project implementation. Topics include: coping with political, economic, environmental and institutional constraints; dealing with institutional and organizational realities; personal constraints; technical assistance shortcomings; decentralization and participation; ineffective information systems; and sustaining project benefits.
Includes bibliographical references.
lje 14/05/2018
Loans
Keywords: Rural development projects